Influencing park visitor behavior, a belief based approach. - Hughes, Michael; Ham, S.; Brown, T. (Sagamore Publishing, 2009)
Communication is a key component in management strategies designed to influence park visitor behavior and minimize social and ecological impacts. However, messages targeting management problems are often delivered without a real understanding of the specific underlying visitor beliefs. This paper applies the theory of planned behavior in the design and evaluation of messages targeting park visitor induced management problems. The method enables specific identification of how messages influence visitor beliefs and behavior. This enables managers to target and refine their messages in a measured, purposeful way for maximum effectiveness. Belief elicitation and measurement surveys were conducted at two Australian park sites, Badger Weir picnic area and Yellagonga Regional Park. The survey results informed the content of messages targeting specific problem behaviors at each site. Message interventions were installed at each site and their effectiveness evaluated based on a second belief measurement survey, and observations of visitor behavior. While the interventions were effective, repeat visitors with strong intentions and habitual behaviors seemed less prone to influence using this method. Despite overall increases in compliance at the two sites, the tested interventions were not successful in influencing salient beliefs or corresponding attitudes of these highly experienced visitors. This presents an additional challenge to parks managers. Visitors who engage in habitual behavior require an alternative approach involving different messages and different message delivery systems relative to their counter-parts. While more overt enforcement could be applied to address entrenched behaviors, alternative efforts might begin in the communities where local repeat visitors live, using a campaign style of communication.